FACTORS INHIBITING THE IMPLEMENTATION OF EFFICIENT CONSUMER RESPONSE - Manning, Craig Dean (My University, 2011)
The purpose of this research was to identify the barriers to the implementation of Efficient Consumer Response (ECR) between manufacturers and retailers in South Africa and to determine whether there were differences in their perceptions relating to ECR. The survey included both qualitative and quantitative phases. The quantitative survey formed the bulk of the analysis with factor analysis and significance testing employed to interpret the survey data. The main finding was that six barriers inhibit the implementation of ECR. These barriers are:  power and trust;  risk;  commitment;  acceptance of change;  objectives and goals and  systems and structure. It was found that there were significant differences between retailer and manufacturer perceptions regarding ECR in relation to the power and trust factor. There were no significant differences between retailer and manufacturer perceptions regarding the remaining five factors identified as being barriers to ECR implementation
MBA thesis - WBS
Keywords: Cunsumer behaviour